Comparative Phytochemical and Biological Profiling of Zea mays L. Varieties in Cotopaxi Region - Raluca A. Mihai; Ramiro Fernando Vivanco Gonzaga; Damián O. Calero Rondal; Dámaris A. Teneda Jijón; Nelson Santiago Cubi Insuaste; Christian D. Borja Tacuri; Rodica D. Catana (Agriculture)
Background: This research evaluated the metabolic and antioxidant activity in red, white, and yellow corn varieties cultivated in the Cotopaxi region. Methods: Colorimetric methods were used for the total phenolic content and total flavonoids, while the LC-MS method was used for the metabolic profile. Also, assays like ABTS, FRAP, and DPPH were used to determine their ability to neutralize free radicals and reduce oxidants. Results: Red corn contains a significantly higher level of natural bioactive compounds compared to other varieties. Phenolics and flavonoids are crucial in antioxidant capacity, contributing significantly to scavenging free radicals and reducing oxidants. Comparative analysis of the biological properties and bioactive compounds in these maize varieties provides treasured insights into the fitness ability advantages of consuming red corn, emphasizing the importance of phenolics and flavonoids in its antioxidant activity. Conclusions: Our findings suggest that red corn could offer greater health benefits compared to white and yellow corn, underscoring the importance of ongoing studies of the biological properties and bioactive compounds in different maize varieties.